THE EFFECTIVENESS OF THE COOPERATIVE SCRIPT METHOD TO IMPROVE THE MAHARAH QIRA'AH OF STUDENTS CLASS VIII D MTs HIKMATUL AMANAH PACET MOJOKERTO - Miftakhul Haadi; Muqimah Liwais Sunnah (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2022)
Arabic learning is often alluded to in the personality of students. Speaking of this may have no connection, but Arabic learning brings the narrative to the students as a complex subject. All parties certainly feel this among pesantren and the general public who learn Arabic. The specialty of Arabic, which lies in the preparation of sentences and the technique of reading, is reversed in this language. At the same time, the method becomes a reference for teachers in taking out the learning system because, with an apparent reference, learning will be transferred enough. This happened in MTs Hikmatul Amanah, where the teaching method carried out by MTs Hikmatul Amanah teachers is an old method where teachers say and explain either with the media or not. Students who feel monotonous learning tend not to like the learning. So the researchers tried to answer the problem by presenting suitable script methods and applied to Maharah Qira'ah. Using this cooperative script method, researchers focus on this application and its effectiveness in improving the ability of Maharah Qira'ah of Student Class VIII D MTs Hikmatul Amanah Pacet Mojokerto. This research uses quantitative research methodology with this type of experimental research. The results showed that 1) The achievement of the results of Maharah Qira'ah of students experienced a significant increase after implementing the cooperative script method in learning, with a percentage increase in student KKM by 72.41%. 2) The application of the cooperative script method in learning proved effective. It can increase the ability of students based on the results of product-moment correlation testing by 71.56 and meet the provisions of thing >ttabel with a contribution amount of 65.48%. Normalized N-gain increased by 27.24%, and the average gain value of 0.64.